Hybrid Tetrameric Perylene Diimide Assemblies. Issue 17 (4th February 2021) - Cann, Jonathan; Farahat, Mahmoud E.; Welch, Gregory C.
Abstract: Organic photovoltaics have found utility as indoor light recycling devices providing an opportunity for the sustainable powering of IoT sensors and related smart electronics. In the report, two organic π‐conjugated molecules consisting of four perylene diimide (PDI) chromophores each are presented and used as non‐fullerene acceptors in indoor photovoltaic devices. The new materials consist of a dimeric N‐annulated PDI core with single PDIs grafted onto the pyrrolic N‐atom positions of the core. Compounds PDI4 e and PDI4 i are PDI tetramers and differ with PDI4 e having the terminal N‐annulated PDI with pyrrolic N‐atom distal to the core and PDI4 i having the terminal N‐annulated PDI with pyrrolic N‐atom proximal to the core. The structural and optoelectronic properties were investigated using NMR spectroscopy, optical absorption and emission spectroscopy, and cyclic voltammetry. The compounds exhibit typical optical signatures for PDIs but notable is that the addition of grafted PDI molecules prevents significant aggregation of the dimeric PDI core, as compared to a reference dimer. Use as non‐fullerene acceptors in ternary bulk‐heterojunction blends with the polymer FBT and fullerene PC61 BM lead to increased open‐circuit voltages and power conversion efficiencies upwards of 13.7 % at 2000 lux light intensity. Abstract : Perylene diimide tetramers : The design and synthesis of two hybrid PDI tetramers is reported. An N‐annulated PDI dimer serves as the core with PDI monomers grafted off the pyrrolic N‐atom positions. Varying the PDI monomer leads to different self‐assembly tendencies. Both compounds exhibit strong visible‐light optical absorption and low‐lying frontier molecular orbitals, making them suitable as non‐fullerene acceptors. Use as 3 rd components in the active layer of organic photovoltaic devices leads to boosts in open‐circuit potential and power conversion efficiency.